Capacity Planning and Product Allocations under Testing Time Uncertainty in Electronic Industry - Asih, H.M.; Chong, K.E.; Faishal, M. (Journal of Advanced Manufacturing Technology (JAMT), 2018)
This research was conducted in a multinational hard disk drive manufacturer in Malaysia facing problem of low utilization in automatic testing process. High volumes, high product mix, short life cycle, and long testing duration compound to the existing problem. The automatic tester is called mixed – load tester because of its ability that can load and unload multiple product families simultaneously. Currently, the planner often conducts re-adjustment capacity planning and allocation because of uncertain testing time. The research has objective to optimize the number of testers while achieving the production target under testing time uncertainty in order to improve tester utilization. To handle the uncertainty, robust optimization was employed in the mixed – load tester model. The result shows this proposed model permits adjustment of company`s production manager`s and capacity planner`s attitude towards testing time uncertainty through the robust parameter.